Contributions of emotional state and attention to the processing of syntactic agreement errors: evidence from P600 - Verhees, Martine W. F. T.; Chwilla, Dorothee J.; Tromp, Johanne; Vissers, Constance T. W. M. (Frontiers in Psychology, 2015)
The classic account of language is that language processing occurs in isolation from other cognitive systems, like perception, motor action and emotion. The theme of this paper is the relationship between a participant’s emotional state and language comprehension. Does emotional context affect how we process neutral words? Recent studies showed that processing of word meaning –traditionally conceived as an automatic process– is affected by emotional state. The influence of emotional state on syntactic processing is less clear. One study reported a mood-related P600 modulation, while another study did not observe an effect of mood on syntactic processing. The goals of this study were: First, to clarify whether and if so how mood affects syntactic processing. Second, to shed light on the underlying mechanisms by separating possible effects of mood from those of attention on syntactic processing. ERPs were recorded while participants read syntactically correct or incorrect sentences. Mood (happy vs. sad) was manipulated by presenting film clips. Attention was manipulated by directing attention to syntactic features vs. physical features. The mood induction was effective. Interactions between mood, attention and syntactic correctness were obtained, showing that mood and attention modulated P600. The mood manipulation led to a reduction in P600 for sad as compared to happy mood when attention was directed at syntactic features. The attention manipulation led to a reduction in P600 when attention was directed at physical features compared to syntactic features for happy mood. From this we draw two conclusions: First, emotional state does affect syntactic processing. We propose mood-related differences in the reliance on heuristics as the underlying mechanism. Second, attention can contribute to emotion-related ERP effects in syntactic language processing. Therefore, future studies on the relation between language and emotion will have to control for effects of attention.